Effect of aging on the stride pattern of veteran marathon runners - Conoboy, P (BMJ Group, 2006)
OBJECTIVE: To investigate the stride pattern of different age groups of veteran runners in a marathon road race. METHODS: This kinematic study investigated the stride pattern (stride length, stride period, velocity, stance time, and non‐stance time) for 151 runners (78 men aged up to 75–80, 73 women aged up to 60–64) at the 7 mile point. RESULTS: Significant declines for men with aging were found for mean stride length (from 2.4 m at age 40–49 to 2.0 m at age 60+), velocity, and non‐stance time (p<0.05), whereas stride period changed little. The findings indicate that the lower velocities of older runners are associated with shorter strides whereas cadence changes little. However, when a statistical adjustment was made for the variation in runners' velocity, it was found that older runners did not have a significantly shorter stride length at any given velocity. CONCLUSION: Although a shorter stride is the mechanical route by which older runners lose velocity, the shorter stride may not be the fundamental cause of the velocity reduction with age. This has implications for researchers and coaches when investigating and training veteran distance runners.